Sticky wages: Evidence from quarterly microeconomic data - Le Bihan, Herve; Montornès, J.; Heckel, T. (2012)
Using an original micro-dataset from France, we investigate nominal wage stickiness. Nominal wage changes are found to occur at a quarterly frequency of around 38 percent over our sample period, and to be to a large extent staggered across establishments, and very synchronized within establishments. We carry out an econometric analysis of wage changes based on a two-threshold sample selection model. Our results are that the timing of wage adjustments is time-dependent as opposed to state-dependent, there is evidence of predetermination in wage changes, and both backward and forwardlooking behavior is relevant in wage setting.